Modalities and Determinants of Career Paths in Pediatrics: A Survey of Former Pediatric Residents From Lille University Medical Center - Héritier-Laffargue, Charlotte; Takvorian, Chloé; Kyheng, Maeva; Nguyen, Sylvie; Dubos, François; Martinot, Alain (Frontiers in Pediatrics, 2021)
There is currently a shortage of pediatricians in the Nord-Pas-de-Calais (NPC) area of France. The shortage affects both hospital positions (since many departures are not replaced) and private practice. The objectives of the present study were to (i) describe the career paths of former pediatric residents from Lille University Medical Center, (ii) identify factors associated with leaving NPC and leaving hospital-based practice, and (iii) compare the characteristics associated with the various types of practice. Methods: Pediatric residents having started their residency at Lille University Medical Center between 1993 and 2013 were invited to fill out an online questionnaire. Main outcomes were leaving NPC and leaving hospital practice. The event rate at different times over a 10-year period was determined using the Kaplan-Meier method. Results: The response rate was 92% (284 out of 310 invited respondents): 61% had changed their place or type of practice at least once, 54% had moved to a different city, and 41% had left NPC. Having trained elsewhere than in Lille and the lack of a chief assistant specialist position in NPC were independently associated with leaving NPC. 73% of the respondents were currently in hospital-based practice. Having started residency after 2003, taking a sabbatical during the residency and not training in a subspecialty (other than general pediatrics) were independently associated with leaving hospital-based practice. The stated reasons for leaving hospital-based practice were on-call duties (according to 71% of the respondents), overwork (46%), family reasons (34%), and a poor atmosphere at work (34%). Hospital-based pediatricians were more active in research and teaching. They worked an average of 13 hours more per week than the other respondents, and were less satisfied with their choice of professional activity and their work-life balance. Conclusion: Changes in the place or type of practice have become frequent. With the recent resurgence of interest in private practice, leaving hospital is reportedly associated with better working conditions, greater satisfaction, and a better work-life balance.